2019
DOI: 10.3390/w12010044
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Analysis of the Diet of Triturus carnifex and Pollution in Mountain Karst Ponds in Central Apennines

Abstract: Mountain karst ponds are sensitive environments, hosting complex trophic networks where amphibians play a major role, often as top predators. The diet of the Italian crested newt (Triturus carnifex) is still poorly known for populations occupying mountain karst ponds. These are traditionally used as livestock's watering points, leading to water pollution due to excreta and wading behavior. The aim of this paper is to understand the relationship between T. carnifex diet composition, assessed through the stomach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…and Alytes obstetricans tadpoles and polyethylene MPs on Physalaemus cuvieri tadpoles under experimental conditions (Hu et al 2016 ; De Felice et al 2018 ; Boyero et al 2020 ; da Costa Araújo et al 2020 ). Additionally, only Hu et al ( 2018 ) detected MPs in tadpoles from small water bodies around the Yangtze River Delta in China and Iannella et al ( 2020 ) found plastic items in stomach content of Triturus carnifex living in livestock’s watering points in Italy.…”
Section: Introductionmentioning
confidence: 99%
“…and Alytes obstetricans tadpoles and polyethylene MPs on Physalaemus cuvieri tadpoles under experimental conditions (Hu et al 2016 ; De Felice et al 2018 ; Boyero et al 2020 ; da Costa Araújo et al 2020 ). Additionally, only Hu et al ( 2018 ) detected MPs in tadpoles from small water bodies around the Yangtze River Delta in China and Iannella et al ( 2020 ) found plastic items in stomach content of Triturus carnifex living in livestock’s watering points in Italy.…”
Section: Introductionmentioning
confidence: 99%
“…In general, our results demonstrate that the vegetation cover levels are less important for lentic semi-aquatic species. Several species that belong to this group can occupy both open and forested habitats (e.g., Giacoma et al 1988;Miró et al 2017;Iannella et al 2020), and some species penetrate into semi-arid plains (Ben Hassine & Nouira 2012; Suriadna & Mykytynets 2018). These species have developed special behaviours to withstand harsh conditions, such as prolonged dormancy periods (e.g., Pleurodeles waltl; Sparreboom 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, MPs were found in the diet of Triturus carnifex Laurenti, 1768 (Iannella et al, 2020) and tadpoles (Hu et al, 2018;Karaoğlu & Gül, 2020). Further evaluation of the occurrence of MPs in anurans and other amphibians is suggested.…”
Section: Amphibiansmentioning
confidence: 95%